Smart stimuli-responsive carrier-free nanoassembly of SN38 prodrug as efficient chemotherapeutic nanomedicine - Guanting Li; Qianhui Jin; Fengli Xia; Shuwen Fu; Xuanbo Zhang; Hongying Xiao; Chutong Tian; Qingzhi Lv; Jin Sun; Zhonggui He; Bingjun Sun (Acta Materia Medica)
The compound 7-ethyl-10-hydroxy-camptothecin (SN38) is a broad-spectrum antitumor agent whose applications are greatly limited by its poor solubility. Therefore, irinotecan, the hydrophilic derived prodrug of SN38, has been developed as the commercial formulation Campto ® for colorectal cancer. However, only 1% to 0.1% of irinotecan is converted to active SN38 in vivo, thus leading to unsatisfactory antitumor activity in clinical settings. Herein, we report a smart stimuli-responsive SN38 prodrug nanoassembly for efficient cancer therapy. First, SN38 was conjugated with an endogenous lipid, cholesterol (CST), via a redox dual-responsive disulfide bond (namely SN38-SS-CST). The prodrug self-assembled into uniform prodrug nanoassemblies with good colloidal stability and ultrahigh drug loading. SN38-SS-CST NPs released sufficient SN38 in the redox environments of tumor cells but remained intact in normal tissues. Finally, SN38-SS-CST NPs potently inhibited the growth of colon cancer without causing systemic toxicity, thus indicating their promise as a translational chemotherapeutic nanomedicine.